An application of recurrent fuzzy neural networks in wind turbine pitch angle control - Nguyễn Thị Xuân Nhi; Nguyen, Chi Ngon; Nguyễn Nhựt Tiến; Trần Thành Luân (Journal of Military Science and Technology, 2022)
Nowadays, renewable energy has been developing strongly, including wind energy. However, the use of this energy source is still dependent on natural conditions because the wind intensity changes continuously, making the power generated from the turbine is unstable. That has a huge impact on the electrical system. This paper presents a solution to control and monitor the pitch angle of the wind turbine to generate the rated power aiming to maintain the grid voltage at a stable level. A supervisory controller using recurrent neural fuzzy networks is proposed and tested on MATLAB/Simulink, under the condition of changing wind speeds.